Synthesis and Characterization of Perovskite Manganate Based on La0.7Ca0.3MnO3 with Ni and Ti doping as Microwave Absorber Material - Saptari, Sitti Ahmiatri; Mar’ah, Mufidatul; Taryana, Yana; Sudrajat, Nanang (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Research has been carried out on the effect of Ni and Ti doping on the microwave absorption properties of the perovskite manganate material La0.7Ca0.3Mn1-xNix/2Tix/2O3 (LCMNTO) with variations x = 0; 0.03; 0.05; and 0.1, which were synthesized by the sol-gel method. The effect of Ni and Ti doping on the structure, grain size, magnetic properties, and microwave absorption properties were investigated in detail by various analytical methods. XRD (x-ray diffraction) characterization showed that the material La0.7Ca0.3Mn1-xNix/2Tix/2O3 has a single phase with an orthorhombic crystal system. The SEM (scanning electron microscope) results showed a tendency to decrease in grain size when the composition of Ni and Ti dopants began to increase. VSM (vibrating sample magnetometer) characterization shows that La0.7Ca0.3Mn1-xNix/2Tix/2O3 is a soft magnet with magnetic properties that decrease with increasing Ni and Ti dopant composition. The characterization of VNA (vector network analyzer) in the 8-12 GHz shows that the highest ability to absorb microwaves is 98% at 8.24 GHz, and there is an addition of absorption areas point and widening of the absorption bandwidth. Thus, the material La0.7Ca0.3Mn1-xNix/2Tix/2O3 has the potential to become a microwave absorber material.